A commercial blend of macroalgae and microalgae promotes digestibility, growth performance, and muscle nutritional value of European seabass (Dicentrarchus labrax L.) juveniles - Mota, Cátia S. C.; Pinto, Olívia; Sá, Tiago; Ferreira, Mariana; Delerue-Matos, Cristina; Cabrita, Ana R. J.; Almeida, Agostinho; Abreu, Helena; Silva, Joana; Fonseca, António J. M.; Valente, Luisa M. P.; Maia, Margarida R. G. (Frontiers in Nutrition, 2023)
Algae can leverage aquaculture sustainability and improve the nutritional and functional value of fish for human consumption, but may pose challenges to carnivorous fish. This study aimed to evaluate the potential of a commercial blend of macroalgae (Ulva sp. and Gracilaria gracilis) and microalgae (Chlorella vulgaris and Nannochloropsis oceanica) in a plant-based diet up to 6% (dry matter basis) on digestibility, gut integrity, nutrient utilization, growth performance, and muscle nutritional value of European seabass juveniles. Fish (11.3 ± 2.70 g) were fed with isoproteic, isolipidic, and isoenergetic diets: (i) a commercial-type plant-based diet with moderate fishmeal (125 g kg−1 DM basis) and without algae blend (control diet; Algae0), (ii) the control diet with 2% algae blend (Algae2), (iii) the control diet with 4% algae blend (Algae4), and (iv) the control diet with 6% algae blend (Algae6) for 12 weeks. The digestibility of experimental diets was assessed in a parallel study after 20 days. Results showed that most nutrients and energy apparent digestibility coefficients were promoted by algae blend supplementation, with a concomitant increase in lipid and energy retention efficiencies. Growth performance was significantly promoted by the algae blend, the final body weight of fish fed Algae6 being 70% higher than that of fish fed Algae0 after 12 weeks, reflecting up to 20% higher feed intake of algae-fed fish and the enhanced anterior intestinal absorption area (up to 45%). Whole-body and muscle lipid contents were increased with dietary algae supplementation levels by up to 1.79 and 1.74 folds in Algae 6 compared to Algae0, respectively. Even though the proportion of polyunsaturated fatty acids was reduced, the content of EPA and DHA in the muscle of algae-fed fish increased by nearly 43% compared to Algae0. The skin and filet color of juvenile European seabass were significantly affected by the dietary inclusion of the algae blend, but changes were small in the case of muscle, meeting the preference of consumers. Overall results highlight the beneficial effects of the commercial algae blend (Algaessence®) supplementation in plant-based diets for European seabass juveniles, but feeding trials up to commercial-size fish are needed to fully assess its potential.